2007
DOI: 10.1111/j.1365-2788.2007.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Does operational diagnosis of schizophrenia significantly impact intellectual deficits in psychotic disorders?

Abstract: The current study failed to show diagnostic usefulness of WAIS-R in discriminating schizophrenia and other psychoses. A diagnosis of schizophrenia does not significantly impact intellectual deficits in psychotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The authors argued that such findings may be due to testing methods, suggesting that the “Weschler Adult Intelligence Scale—Revised (WAIS-R)” is not useful in discriminating SZ from other psychoses. Their results were in accordance with Kitamura et al (2007) , who also found that intelligence performance measured with the WAIS-R could not distinguish between SZ and non-schizophrenic psychotic disorders. However, the study mixed multiple diagnoses in the non-schizophrenic subgroup including “psychotic disorder due to a general medical condition” and “psychotic disorders not otherwise specified”.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…The authors argued that such findings may be due to testing methods, suggesting that the “Weschler Adult Intelligence Scale—Revised (WAIS-R)” is not useful in discriminating SZ from other psychoses. Their results were in accordance with Kitamura et al (2007) , who also found that intelligence performance measured with the WAIS-R could not distinguish between SZ and non-schizophrenic psychotic disorders. However, the study mixed multiple diagnoses in the non-schizophrenic subgroup including “psychotic disorder due to a general medical condition” and “psychotic disorders not otherwise specified”.…”
Section: Introductionsupporting
confidence: 89%
“…In ATPDs, some studies reported less impaired cognitive functioning in comparison with SZ while others found no difference in cognitive variables ( Ayesa-Arriola et al, 2016 ; Kitamura et al, 2007 ; Ngoma et al, 2010 ). The study by Ayesa-Arriola et al (2016) examined whether there were distinguishable neurocognitive profiles in diagnostic subgroups of first-episode psychosis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Current lifetime prevalence data suggest that between 20%-70% of individuals with IDD experience significant behavioral problems or meet current diagnostic criteria for a mental disorder (1,(3)(4)(5). These high prevalence rates are linked to the severity of intellectual disability, global impairments in adaptability and resilience, coexisting neurological/ medical conditions, histories of major psychosocial and familial dysfunction, and abuse and neglect (5)(6)(7).…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…For example, schizophrenia is frequently diagnosed and treated based on the presence of hallucinations or delusions without a comprehensive exploration of psychosis; psychotic forms of major depressive, bipolar disorder, PTSD, delirium, dissociative states and intoxication can occur (3). As a team member, the psychiatrist often plays the role of translator between the world of the neurosciences and biomedicine and the team.…”
Section: Treatment and Outcomesmentioning
confidence: 99%